2008
DOI: 10.1016/j.brainres.2008.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mRNA expression of splice forms of the ζ1 subunit of the N-methyl-d-aspartate receptor and spatial memory in aged mice

Abstract: Age-related changes in the protein and mRNA expression of some of the splice forms of the ζ1 (NR1) subunit of the NMDA receptor have been seen in mice and rats. The present study was designed to determine whether individual splice forms of the ζ1 subunit of the NMDA receptor within prefrontal/frontal cortical regions contribute to memory deficits during aging and whether experience in learning tasks can influence the expression of the splice forms. mRNA expression of 4 splice forms (ζ1-1, ζ1-3, ζ1-a and ζ1-b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 70 publications
1
54
0
Order By: Relevance
“…In addition, although three out of four experiments in our laboratory using a 12-day training period showed that old C57BL/6 mice were impaired in both place training and probe trials. (Magnusson, 1998a, 2001, Das and Magnusson, 2008), one study showed deficits in only the place training trials (Magnusson et al, 2003). This suggests that the place training trials may be more sensitive than probe trials for detecting age-related differences in long-term memory.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although three out of four experiments in our laboratory using a 12-day training period showed that old C57BL/6 mice were impaired in both place training and probe trials. (Magnusson, 1998a, 2001, Das and Magnusson, 2008), one study showed deficits in only the place training trials (Magnusson et al, 2003). This suggests that the place training trials may be more sensitive than probe trials for detecting age-related differences in long-term memory.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant effect of ibuprofen on long-term memory in these mice, however, there was a trend for ibuprofen to worsen performance in the oldest mice in the place trials. In probe trials, used to assess the development of a spatial bias, there were no differences in performance for treatment or age, unlike in other studies (Magnusson et al, 2007, Das and Magnusson, 2008, Das and Magnusson, 2011, Brim et al, 2013, Zamzow et al, 2013), but see (Zhao et al, 2009). Some of the oldest mice were unable to complete all of the place trials in this study.…”
Section: Discussionmentioning
confidence: 66%
“…The GluN2B subunit (Magnusson, 2000, Magnusson et al, 2002) and GluN1-1 and GluN1-3 splice variants (Magnusson et al, 2005, Das and Magnusson, 2008) have previously been shown to be selectively vulnerable to the effect of aging in C57BL/6 mice. If inflammation was playing a role during aging on NMDA receptors, it was expected that ibuprofen would improve the expression of GluN2B, all GluN1 subunits as a whole, and the GluN1-1 and GluN1-3 splice variants, particularly in the oldest animals, but not affect GluN1-2 splice variants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations